2016
DOI: 10.1007/s11250-016-1156-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and molecular characterisation of lumpy skin disease virus in Zimbabwe using the P32 gene

Abstract: Between January, 2013 and December, 2014, there was a lumpy skin disease (LSD) outbreak that affected cattle in different localities of Zimbabwe. The outbreak resulted in severe economic losses to the livestock industry. A retrospective study was conducted by examining stored veterinary records of the LSD outbreak at the Central Veterinary Laboratory (CVL) in Harare, Zimbabwe. Over the 2-year period, a total of 10,038 cases and 880 deaths (8.77 %) were recorded. LSD was reported from all regions of the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 22 publications
6
32
1
Order By: Relevance
“…Mafirakureva, Saidi, and Mbanga () reported morbidity of 4.97%–30.95% with mortality rates of 8.77%, whereas in our case, the mean morbidity and mortality were 10 (0.5%–100%) and 0.875 (0%–50%), respectively. In other studies, morbidity and mortality rates were shown to increase up to 30% (Abutarbush et al., ; Şevik & Doğan, ).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Mafirakureva, Saidi, and Mbanga () reported morbidity of 4.97%–30.95% with mortality rates of 8.77%, whereas in our case, the mean morbidity and mortality were 10 (0.5%–100%) and 0.875 (0%–50%), respectively. In other studies, morbidity and mortality rates were shown to increase up to 30% (Abutarbush et al., ; Şevik & Doğan, ).…”
Section: Discussioncontrasting
confidence: 64%
“…() and Mafirakureva et al. (). Based on these findings, as far as diagnostics is concerned, it is logical to examine a few types of samples, for example nodules and nasal swabs, to maximize the chances of detecting the LSDV genome in suspected animals (Table ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reports by Woods, (1988) and Tuppurainen et al (2013) suggested that insects play a role in the mechanical transmission of LSD. Moreover, studies in South Africa, Ethiopia, Zimbabwe and Nigeria reported that cases of CE and LSD occur more commonly during raining season compared to dry season (Scagliarini et al, 2012;Hailu et al, 2014;Mafirakureva et al, 2016;Adedeji et al, 2018). The common clinical signs of viral skin diseases observed by the farmers were skin nodules, fever, anorexia and weight loss for LSD and GTP.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the LSDVs identified in Namibia and those in neighbouring South Africa share a common origin, but in order to confirm this, full-genome sequencing and further molecular epidemiological studies in the region are required. A recent characterization of the P32 gene of LSD samples in Zimbabwe identified two genetically distinct viruses circulating in the country [ 7 ]. A similar comparative study should be undertaken for other LSDV isolates collected in southern Africa in order to get a clearer picture of virus circulation at a regional level.…”
mentioning
confidence: 99%